Perilaku Penawaran Peternak Sapi di Indonesia dalam Merespon Perubahan Harga (Supply Behaviour of Cattle Farmers in Indonesia to Respond the Price Changes) - Ahmad Zainuddin; Ratna Winandi Asmarantaka; Harianto Harianto (Jurnal Agribisnis Indonesia, 2015)
Demand for beef in Indonesia keeps growing and it leads to increased gap between its low production and high consumption (excess demand). The impact is an increasing trend of domestic beef price. Eventhough, the beef farmers in Indonesia don’t respond to the price changes. In this study, an attempt has been made to examine the supply response of beef farmers in Indonesia by using Error Correction Model (ECM). The result showed that (1) the beef supply influenced by the number of cattle cut which is variable availability; (2) the price of dairy milk, the price of feed, and the price of beef the world have negative influence; (3) cattle farmers not responsive to the price change as spatially subsistence.